2018
DOI: 10.1097/mpg.0000000000001784
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Pediatric Colonic Eosinophilia

Abstract: There are 3 main phenotypes of children with colonic eosinophilia. Signs of chronic systemic inflammation raise suspicion for IBD. Peripheral eosinophilia and male sex are associated with EC. A significant percent of children with colonic eosinophilia do not have colonic disease. Eosinophils/high-power field is not reliable to differentiate etiologies. Repeat colonoscopies may be required to reach final diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The reasons why eosinophils seem to be more active in younger patients and also during remission are not known and, as yet, have been largely uninvestigated. It has been reported that colonic eosinophilia is more prevalent in younger than in older children diagnosed with IBD or other colonic diseases [45,46]. Furthermore, tissue eosinophilia seems to be a dominant feature of subclinical histological inflammation for patients with IBD in remission [47], which might be more prevalent in young patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons why eosinophils seem to be more active in younger patients and also during remission are not known and, as yet, have been largely uninvestigated. It has been reported that colonic eosinophilia is more prevalent in younger than in older children diagnosed with IBD or other colonic diseases [45,46]. Furthermore, tissue eosinophilia seems to be a dominant feature of subclinical histological inflammation for patients with IBD in remission [47], which might be more prevalent in young patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical follow-up data was available for 202/212 visits (95.3%) of patients with IBD. The median (IQR) follow-up time was 48 (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) months. The total event rate was 94/202 (46.5%).…”
Section: Fecp Is a Prognostic Biomarker In Young Patients With Ibdmentioning
confidence: 99%
“…8 Some studies have demonstrated a male predominance of certain nonesophageal EGIDs such as EC, but in general there appears to be a lack of male predominance in these disorders. [32][33] When evaluating the initial management of these disorders, wide variability existed amongst participating centers, which may speak to differences in provider preference/experience, the lack of high level evidence to support any given therapy, as well as to the heterogeneity of the presentation of these disorders. PPIs were the most commonly used medication, even in patients with colonic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Mansoor et al, a similar female predominance was found in both EGE and EC 8 . Some studies have demonstrated a male predominance of certain non-esophageal EGIDs such as EC, but in general there appears to be a lack of male predominance in these disorders 32-33 .…”
Section: Discussionmentioning
confidence: 99%